Claudedebeella, a replacement name for Falklandia De Broyer, 1985 (Crustacea, Amphipoda, Lysianassoidea, Tryphosidae), preoccupied by Falklandia Forster & Platnick, 1985 (Arachnida, Araneae) - Thurston, Michael H.; Horton, Tammy (Zootaxa, 2020)
Falklandia Forster & Platnick, 1985 was established for a genus of spider (Dysderoidea, Orsolobidae) in a paper published in July 1985. The homonymy with Falklandia De Broyer, 1985 (Lysianassoidea, Tryphosidae) published in October 1985 has been recognised only recently and requires a replacement name for the latter concept. An additional junior homonym, Falklandia Whatley, Chadwick, Coxhill & Toy, 1987, is discussed by Brandão (in press)